Rethinking Elderly Caregiving In Javanese Patriarchal Culture Through Maqāṣid Al-Sharīʿah Gender Justice And Sustainable Family Care - Misbahul Munir (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2025)
This research examines elderly caregiving practices in Javanese society, using case studies from Wonogiri and Jombang Regencies, through an integrative framework that combines Javanese customary values, critical gender analysis, and Maqashid al-Shari’ah. The study finds that while values such as ngopeni, andhap asor, and mbales budi represent a strong relational ethic of respect and intergenerational care, their operationalization within modern patriarchal family structures has normalized gender inequality. Daughters are systematically positioned as primary caregivers, performing intensive physical, emotional, and social labor that remains largely invisible and undervalued, whereas sons' roles are often limited to financial support. This feminization of care is reinforced by cultural narratives that frame it as a natural feminine duty and a form of filial piety (bakti), thereby silencing criticism of intra-familial injustice. Using Maqashid al-Shari’ah principles—including justice (al-‘adl), removal of hardship (raf‘ al-haraj), and protection of life, intellect, and resources (hifz al-nafs, hifz al-‘aql, hifz al-mal)—the study critiques caregiving practices that impose unequal burdens and proposes a reinterpretation of Javanese values toward a more equitable and sustainable model. It concludes that achieving just elderly care requires redistributing caregiving responsibilities within families, recognizing unpaid care work as valuable socio-economic labor, and strengthening structural support from the state and community. This research contributes to interdisciplinary discussions on care, gender, and Islamic ethics by offering a culturally grounded normative framework for transforming caregiving into a practice of collective justice and human dignity.